C5a, but not C5a‐des Arg, induces upregulation of heteromer formation between complement C5a receptors C5aR and C5L2. Issue 10 (24th September 2013) - Croker, Daniel E; Halai, Reena; Fairlie, David P; Cooper, Matthew A
Abstract : Receptors for C5a have an important role in innate immunity and inflammation where their expression and activation is tightly regulated. There are two known receptors for C5a: the C5a receptor (C5aR) and the C5a receptor like‐2 (C5L2) receptor. Here we hypothesized that activation of C5aR might lead to heteromer formation with C5L2, as a downregulatory mechanism for C5aR signaling. To investigate this experimentally, bioluminescent resonance energy transfer (BRET) was implemented and supported by wide‐field microscopy to analyze receptor localization in transfected HEK293 cells and human monocyte‐derived macrophages (HMDM). BRET experiments indicated the presence of constitutive C5aR‐C5L2 heteromers, where C5a, but not C5a‐des Arg, was able to induce further heteromer formation, which was inhibited by a C5aR‐specific antagonist. The data obtained suggest that C5aR‐C5L2 can form heteromers in a process enhanced by C5a, but not by C5a‐des Arg. There was also a significant difference in the levels of the anti‐inflammatory cytokine IL‐10 detected in HMDM following exposure to C5a compared with that seen for C5a‐des Arg but no differences in the pro‐inflammatory cytokines TNFα and IL‐6. These subtle differences in C5a and C5a‐des Arg induced receptor function may be of benefit in understanding the regulation of C5a in acute inflammation.